Nurse’s Perception of Papua Province’s Ability to Run Master Program of Occupational Health Nursing - Isak Jurun Hans Tukayo; Mohammad Saljan; I Ketut Swastika; Syaifoel Hardy (Jurnal Berita Ilmu Keperawatan, 2022)
Industrial development in Papua Province has not been accompanied by an increase in the specialization of Occupational Health Nursing (OHN) education, despite the demands for quality health care services. The objective is to explore the nurses’ perception on managing a master's program in Occupational Health Nursing (OHN). The study methods using descriptive cross sectional design. The variables were master program of OHN as the dependent variable and nurse perception as the independent variable. The population were nurses in Papua and the sampling technique was simple random sampling. Total sample are 184 nurses as sampling with confidence level of 95% and confidence interval of 5% from 350 total population. The study used univariate data analysis which includes demographic data and respondents' perceptions of the ability of the Papuan people in implementing the program. The data collection tool was a mixed questionnaire of Likert scale processed by the SPSS (Statistical Package for Social Sciences) 25 version application and R program for sampling processing. The results show majority respondents (76.1%) were interested in continuing the OHN Master's program, and most of them (73.3%) had the perception that the province of Papua was able to run it. The research projected an initial signal that specialist education in OHN was for the benefits of workers, industries, the public, and the nursing profession.